The effects of ad - libitum consumption of chitosan oligosaccharide with drinking water on laying quails - Kiraz, C; Buğdayci, KE (Journal of the Hellenic Veterinary Medical Society, 2023)
The aim of this study was to determine the effects of chitosan oligosaccharide on feed conversion ratio, some egg quality parameters, and some blood parameters in Japanise quails. Chitosan oligosaccharide (ChitO) was added to the drinking water of quails. A total of 192 (7 – 8 weeks old) Japanese quails (Coturnix coturnix Japonica) were divided into one control and 3 treatment groups, each consisting of 48 quails. Each group was divided into 6 replicates. While no additive was added to the control group, ChitO was added to the drinking water of the first, second, and third groups at the levels of 0.015, 0.030 and 0.045 g / L, respectively. They were given water and feed ad libitum. At the end of the study, no significant differences were observed between the control and treatment groups, except in their feed consumption and egg shell weight. In the first treatment group (given 0.015 g / L ChitO), it was observed that feed consumption decreased significantly compared to the control group; however, the difference between the other treatment groups was insignificant. The egg shell weight of the second treatment group (0.030 g / L ChitO) was found to be significantly higher (p < 0.05) than that of the control group. In general, consumption of chitosan oligosaccharide with drinking water tended to decrease feed consumption, without adversely affecting feed efficiency, and tended to increase eggshell weight.